Cytisine parameters measured in the 1.5 Tesla magnetic field - Bober, Zuzanna; Galiniak, Sabina; Leksa, Dawid; Dynarowicz, Klaudia; Aebisher, David; Ostańska, Elżbieta; Czmil, Anna; Bar, Piotr; Bartusik-Aebisher, Dorota; Tutka, Piotr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Cytisine, Cytisinum (C11H14N2O), is an organic chemical compound. Cytisine is heterotricyclic compound that is the toxic principle in Laburnum seeds and is found in many members of the Fabaceae (legume, pea or bean) family. Aim. The aim of the study is to measure the influence of water on the form of drug in the magnetic field 1.5 Tesla. Material and methods. For this purpose, magnetic resonance imaging tests were performed to check the solubility of pure cytisine, Desmoxan tablets and Tabex capsules. Results. From a pharmacological point of view, both Desmoxan tablets and Tabex capsules should exert the same effect on the human body, this is due to the identical content of the active substance, in this case cytisine (1.5 mg). Conclusion. The differences in the results obtained may be related to additional excipients that contain medications, but it is believed that they should not have a negative impact on the action of the active substance.
Keywords: cytisine; desmoxan; magnetic resonance imaging; tabex